A "kissing lesion": In-vivo 7T evidence of meningeal inflammation in early multiple sclerosis. (July 2017) - Kolber, Pierre; Droby, Amgad; Roebroeck, Alard; Goebel, Rainer; Fleischer, Vinzenz; Groppa, Sergiu; Zipp, Frauke
Background: The role of cortical lesions (CLs) in disease progression and clinical deficits is increasingly recognized in multiple sclerosis (MS); however the origin of CLs in MS still remains unclear. Objective: Here, we report a para-sulcal CL detected two years after diagnosis in a relapsing-remitting MS (RRMS) patient without manifestation of clinical deficit. Methods: Ultra-high field (7T) MR imaging using magnetization-prepared 2 rapid acquisition gradient echoes (MP2RAGE) sequence was performed. Results: A para-sulcal CL was detected which showed hypointense rim and iso- to hyperintense core. This was detected in the proximity of the leptomeninges in the left precentral gyrus extending to the adjacent postcentral gyrus. Conclusion: This finding indicates that inflammatory infiltration into the cortex through the meninges underlies cortical pathology already in the early stage of disease and in mild disease course.